Psoriasis caused by camrelizumab in a patient with esophageal cancer: a case report - Duan, Yimei; Chen, Jie; Zhong, Dongsheng; Xiong, Xincai (Frontiers in Medicine, 2025)
Immune checkpoint inhibitors (ICIs) are an emerging treatment strategy for cancer, working by activating T cells to suppress tumor growth. However, they can cause immune-related adverse events (irAEs), including psoriasis. We report a case of a patient with esophageal cancer who developed psoriasis 6 weeks after starting camrelizumab. The condition improved following the discontinuation of camrelizumab and treatment with a topical glucocorticoid and a vitamin D3 derivative ointment. At 6-month follow-up, the patient showed no recurrence of psoriatic lesions or tumor progression.